The historian and utopia. Reflections inspired by a master class - Vega Centeno Sara Lafosse, Rafael (2020)
Jeffrey Klaiber is recognized for his prolific work, characterized by a methodical retrieval and presentation of information. His care for objectivity in the historical judgment did not mean, however, an absence of involvement or of taking a position in the historical process. The text Globalization and Evangelization in the XVI and XXI centuries. Ideology versus utopia, which is an inaugural lecture of the year 2005 at the Antonio Ruiz de Montoya University, puts in evidence his commitment and bet for utopia, understood as the human action aimed at materializing dreams and longings for a better society.